(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The modern educational landscape is evolving rapidly, emphasizing the need for students to develop strong analytical skills. Problem-based learning (PBL) has proven to be an effective pedagogical approach for enhancing critical thinking, problem-solving, and decision-making abilities. This article explores the significance of PBL in higher education, its role in improving students’ cognitive abilities, and practical methods for integrating it into the curriculum. The research combines theoretical analysis with empirical case studies, demonstrating the effectiveness of PBL in fostering analytical skills.